STRUCTURAL REGULARITIES OF ECONOMIC TRANSFORMATION IN COUNTRIES WITH PERSISTENT DEMOGRAPHIC DECLINE - Petrivskyi, Oleksii (Current Problems of Sustainable Development, 2026)
The article examines the structural regularities of economic transformation under conditions of sustained demographic decline. It is substantiated that depopulation should be interpreted not only as a demographic phenomenon, but also as a long-term macrostructural factor transforming the mechanisms of economic development, labour markets, sectoral structures, financial systems, and state economic policy. The study is based on a comparative analysis of countries experiencing long-term demographic decline, including Japan, South Korea, Germany, Italy, Bulgaria, Romania, Finland, Denmark, and Sweden. Several stable structural regularities characteristic of depopulation economies are identified. The first is the transition from extensive to intensive economic growth, where productivity, automation, and technological modernisation become the main drivers of economic dynamics. The second concerns the structural vulnerability of labour-intensive and low-productivity sectors facing labour shortages and rising labour costs. The third regularity is the expansion of a high-productivity economic core represented by sectors with high value added, including IT, engineering, pharmaceuticals, financial services, and high-tech manufacturing. The article also identifies increasing spatial polarisation of economic activity. Large urban agglomerations preserve relative demographic and economic stability due to migration and capital concentration, while peripheral territories experience accelerated depopulation and infrastructure degradation. Special attention is devoted to the risk of fiscal crowding-out of productive investments caused by rising expenditures on healthcare, pensions, and social support. The article also analyses the transformation of the financial sector in ageing economies, characterised by the expansion of pension services, asset management, and low-risk financial instruments. It is concluded that depopulation forms a distinct trajectory of economic transformation requiring adaptation of economic policy to long-term demographic constraints. The practical implications of these regularities are considered in the context of Ukraine, where demographic decline is intensified by war-related migration losses and post-war structural challenges.